A Case-Control Study of Risk Factors for Salivary Gland Cancer in Canada. (4th January 2017) - Pan, Sai Yi; de Groh, Margaret; Morrison, Howard
Abstract : Aim . To assess the effect of various lifestyle risk factors on the risk of salivary gland cancer in Canada using data from a population-based case-control study. Methods . Data from a population-based case-control study of 132 incident cases of salivary gland cancer and 3076 population controls were collected through self-administered questionnaire and analysed using unconditional logistic regression. Results . Four or more servings/week of processed meat product was associated with an adjusted odds ratio (OR) and corresponding 95% confidence interval (CI) of 1.62 (1.02–2.58). Nonsignificantly increased ORs were also related to obesity, >7 drinks/week of alcohol consumption, and occupational exposure to radiation. Furthermore, nonsignificantly decreased ORs were found to be associated with high education level (>12 years) (O R = 0.65 ), high consumption of spinach/squash (O R = 0.62 ) and all vegetables/vegetable juices (O R = 0.75 ), and >30 sessions/month of recreational physical activity (O R = 0.78 ). Conclusions . This study suggests positive associations with consumption of processed meat, smoking, obesity, alcohol drinking, and occupational exposure to radiation as well as negative associations with higher education, consumption of spinach/squash, and physical activity, which suggest a role of lifestyle factors in the etiology of salivary gland cancer. However, these findings were based on small number of cases and were nonsignificant. Further larger studies are warranted to confirm our findings.